Umidade na folha de amoreira (Morus sp.) em ambientes de armazenamento - Porto, Antonio José (2010)
Mulberry leaves (IZ 56/4 cultivar) in the pos-harvest, had been taken to the laboratory and submitted to six storage environments (8 hours in open ambient-O, 8 hours in cover ambientC, 1hO/7hC, 2hO/6hC, 3hO/5hC and 4hO/4hC), aiming to evaluate moisture exchange capacity . It was utilized the experimental design split plot with five replications (blocks), six principal treatments (parcels) and nine secondary treatments (sub parcels, weighing of hour in hour, of 08h00min. until 16h00min.). In the period of eight hours of experimentation mulberry leaves moisturedevreased in all the ambients evaluated. However, for cover leaves with wet cloth, for all periods, the water purport (74,63%) was maintained close to the original value (08h00min.- 76,07%), demonstrating the efficiency technique in the conservation of the humidity of leaves for feeding silkworm.